2018
DOI: 10.5194/amt-11-2361-2018
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of greenhouse gas concentrations derived from ground-based FTS spectra at Anmyeondo, South Korea

Abstract: Abstract. Since the late 1990s, the meteorological observatory established in Anmyeondo (36.5382° N, 126.3311° E, and 30 m above mean sea level) has been monitoring several greenhouse gases such as CO2, CH4, N2O, CFCs, and SF6 as a part of the Global Atmosphere Watch (GAW) Program. A high resolution ground-based (g-b) Fourier transform spectrometer (FTS) was installed at this observation site in 2013 and has been operated within the frame work of the Total Carbon Column Observing Network (TCCON) since August 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Theoretically, more stations could be used after 2011, but due to scanty long-term observations, we forfeited some stations from the analysis. This forfeiture has not affected global AGR TCCON because, if we include all three available MGRs from the excluded Anmyeondo site [94] to the calculation of global AGR TCCON , the difference between the final global AGR TCCON estimate and an experimental global AGR TCCON (with Anmyeondo) would be negligible (~0.1 ppm for 2016 and 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, more stations could be used after 2011, but due to scanty long-term observations, we forfeited some stations from the analysis. This forfeiture has not affected global AGR TCCON because, if we include all three available MGRs from the excluded Anmyeondo site [94] to the calculation of global AGR TCCON , the difference between the final global AGR TCCON estimate and an experimental global AGR TCCON (with Anmyeondo) would be negligible (~0.1 ppm for 2016 and 2017).…”
Section: Discussionmentioning
confidence: 99%
“…intensity divided by the initial intensity, can be used to efficiently calculate gas concentration. [77]…”
Section: Working Principlesmentioning
confidence: 99%
“…Reproduced under the terms of CC BY license. [ 77 ] Copyright 2018, The Authors, published by Copernicus Publication. iv) Describe the actual equipment placement and semi‐automated monitoring of the observation laboratory.…”
Section: Experimental Approaches Perspectives and Expectations In Ghg...mentioning
confidence: 99%
“…The results from the validation of OCO-2 XCO 2 against ground-based FTS data from the nearest TCCON stations located in Japan found biases of 0.32 ppm, 2.31 ppm, and 0.30 ppm over Rikubetsu, Tsukuba, and Saga, respectively [29]. In addition, Oh et al [62] found that OCO-2 XCO 2 was overestimated by 0.18 ± 1.19 ppm compared to the Anmyeondo (South Korea) TCCON station data. A recent study [5] compared the OCO-2 XCO 2 with aircraft in situ data over Northeast China and found a bias of −4.68 ± 0.44 ppm in OCO-2 measurements.…”
Section: Extrapolationmentioning
confidence: 99%